2020
DOI: 10.26714/seanr.2.2.2020.70-73
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Parenting Patterns on the Personal Social Development of Preschool Children

Abstract: The child's personal social development is greatly influenced by the environment and interactions between the child and the parents or other adults around them. The type of parenting style of parents towards their children will affect the attainment of the level of education, social skills and overall development of the child. The purpose of this study was to determine the effect of parenting style on the personal social development of preschool children. The method used in this research is descriptive correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(12 reference statements)
0
2
0
1
Order By: Relevance
“…However, previous studies showed that parenting style in the family environment significantly affects the children's future success and learning (Sarwar, 2016;Masud et al, 2019). Parenting techniques that consider the family environment will enable children to establish a good relationship with the wider environment (Ghozali, 2020). The family as an al-ula madrasah significantly contributes to building children's future (Gadsden et al, 2016;Ritonga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, previous studies showed that parenting style in the family environment significantly affects the children's future success and learning (Sarwar, 2016;Masud et al, 2019). Parenting techniques that consider the family environment will enable children to establish a good relationship with the wider environment (Ghozali, 2020). The family as an al-ula madrasah significantly contributes to building children's future (Gadsden et al, 2016;Ritonga et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is because the nurturing environment and parenting patterns play an important role in shaping a healthy state in children. 11 According to an investigation by Ghozali et al 18 which involved children aged 3-5 years in Qatar, children raised with authoritative parenting patterns had better personal and social development than those with permissive parenting.Similarly, Haslam et al discovered that children aged 2-10 years in Australia and Indonesia with authoritative parenting had better emotional regulation and experienced fewer behavioral disturbances compared to those with authoritarian parenting. 19 Other factors that may contribute to a child's mentalemotional development include the family's socioeconomic status, the mental health of the parents, and the state of family harmony.…”
Section: Discussionmentioning
confidence: 99%
“…Masa anak yang dimaksud disini adalah anak dengan usia 4-5 tahun. Pada masa ini anak menunjukkan kemampuan untuk lebih banyak bergerak, mengembangkan rasa ingin tahu, dan mengeksplorasi lingkungan sekitar (Ghozali, 2020). Lingkungan sekitar anak sangat beragam, mulai dari teman bermain yang sesuai, tempat atau lingkungan sosial yang baru, dan yang paling dekat dengan anak itu sendiri adalah lingkungan sosial dalam keluarga itu sendiri dalam hal ini orang tua.…”
Section: Pendahuluanunclassified